Tindak Pidana Mempekerjakan Anak Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan: Analisis Putusan Mahkamah Agung Nomor 293/ K/Pid.Sus/2018 - Fithania Wahyu Fitria Saputri; Rosdiana Rosdiana; Mohamad Mujibur Rohman (JOURNAL of LEGAL RESEARCH, 2022)
This study explains how Law Number 13 of 2003 on Employment makes child labor a crime. It also looks at Supreme Court Verdict Number 293 K/Pid.Sus/2018, which was made by the Supreme Court in 2018. Qualitative methods are used in this study, which takes a look at the case from a constitutional (statutory) point of view (case approach). On the basis of Law Number 13 Year, 2003 on Employment and Manpower, employers aren't allowed to hire children. Some people say that children between the ages of 13 and 15 can do light work, but they can't do anything that could harm their health or development in any way. The threat of punishment for people who do things that are illegal There are rules about how to get a job in Law Number 13 of the Year 2003 about Manpower, which you can find in Articles 181, 183, and 182. (1). People who work for the Supreme Court think about things that aren't related to law when they make decisions about Supreme Court No. 293 K/Pid.Sus 2018. That is because it was revealed at the trial that the child witnesses didn't have any problems with their bodies, minds, or social lives. Indonesia's law on employment was used to look at Supreme Court No. 293/K/Pid.Sus/2018, and it was found to be in line with the law.